Resposta da cultura do feijão (Phaseolus vulgaris L.) `à aplicação de calcário, adubo nitrogenado e fosfatado, em municípios da Zona da Mata, Minas Gerais - A Nogueira Fontes, Luiz; Julião Braga, Luiz; Ribeiro Gomes, Fábio (Revista Ceres, 2025)
Four field experiments were laid out in the same soil type, on locations at Viçosa (two trials), Visconde do Rio Branco and São Pedro dos Ferros, in the Zona da Mata, Minas Gerais State, during two growing seasons. The objective was to study the effect of lame, phosphorus and nitrogen on grain yield by dry beans (Phaseolus vulgaris L.)